2011
DOI: 10.1080/15287394.2011.570225
|View full text |Cite
|
Sign up to set email alerts
|

Formation of VascularS-Nitrosothiols and Plasma Nitrates/Nitrites Following Inhalation of Diesel Emissions

Abstract: Epidemiological studies have associated traffic-related airborne pollution with adverse cardiovascular outcomes. Nitric oxide (NO) is a common component of fresh diesel and gasoline engine emissions that rapidly transforms both in the atmosphere and once inhaled. Because of this rapid transformation, limited information is available in terms of potential human exposures and adverse health effects. Young rats were exposed to whole diesel emissions (DE) adjusted to 300 µg/m3 of particulate matter (containing 3.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…Knuckles and colleagues have recently reported that following diesel exhaust exposure, rats had increased plasma NO x (nitrate and nitrite combined) concentrations that appeared to be predominantly the result of absorption of NO from the exposure itself, although they exhibited significant increases in eNOS expression consistent with increased NO production. 38 Controlled exposures to NO and nitrogen dioxide in humans with subsequent measurements of plasma nitrite concentrations may help to define this further.…”
Section: Discussionmentioning
confidence: 99%
“…Knuckles and colleagues have recently reported that following diesel exhaust exposure, rats had increased plasma NO x (nitrate and nitrite combined) concentrations that appeared to be predominantly the result of absorption of NO from the exposure itself, although they exhibited significant increases in eNOS expression consistent with increased NO production. 38 Controlled exposures to NO and nitrogen dioxide in humans with subsequent measurements of plasma nitrite concentrations may help to define this further.…”
Section: Discussionmentioning
confidence: 99%
“…Reductions in pulmonary function have also been reported following occupational exposures in chronic studies (Rudell et al, 1996). In addition, diesel PM has been associated with changes in heart rate, increased incidence of arrhythmias, impairment of vasodilation, increase in blood pressure, and systemic inflammation (Hazari et al, 2011;Peretz et al, 2008;Tornqvist et al, 2007;Nemmar et al, 2007;Carll et al, 2013;Harkema et al, 2009;Knuckles et al, 2011). Human studies by Mills et al (2005Mills et al ( , 2007aMills et al ( , 2007b) demonstrated a dose-dependent increase in prothrombotic effects and acute myocardial ischemia upon exposure to diesel exhaust.…”
Section: Bd Ce Further Studies Are Required To Understand What Combumentioning
confidence: 95%
“…Previous studies focusing on the mechanisms of the effects of diesel CE exposure were performed using the following concentrations: 500 μg/m 3 and 300 μg/m 3 in rats (Carll et al, 2013;Carll et al, 2012;Harkema et al, 2009), and 300 μg/m 3 in mice (Knuckles et al, 2011). In particular, Finch et al (2002) exposed F344 rats to biodiesel at concentrations of 40, 200, and 500 μg/m 3 .…”
Section: Methodsmentioning
confidence: 99%
“…Both DE groups had decreased BP during exposure, suggesting mediation by DE gases. Although the specific gases mediating this effect remain unclear, there is mounting evidence that inhaled NO is converted to nitric oxide (NOx), which remains in the blood up to 2 h postexposure (Knuckles et al, 2011). NOx decreases BP through vasodilation and facilitates parasympathetic control over cardiac function (Conlon and Kidd, 1999;Yabe et al, 1998).…”
Section: De Alters Cardiovascular and Autonomic Functionmentioning
confidence: 99%